Need To Boost Rice Farming - Sunday Star, Hariati Azizan (2008)
UN peacekeepers have been on the alert in the Haitian capital Port-au-France since last Monday. They are defending the Haitian presidential palace, not from a rebel army or foreign trespassers, but from hungry Haitians who took to the streets to protest about the shortage of food and its soaring food proices